Adaptation of Impostor-Profile 30 Scale into Indonesian: Evidence of content validity and response process - Yantu, Ramaway Rojiah Juybe M.; Cahyadi, Surya; Fitriana, Efi (Jurnal Psikologi, 2025)
Background: Academic success is often perceived as a source of pride, but for some students, it can lead to increased pressure. These individuals tend to attribute their success to external factors rather than their own abilities, a phenomenon known as impostor phenomenon. Purpose: This study aims to translate the Impostor-Profile 30 for measuring the impostor phenomenon, into Indonesian using a double translation procedure, as well as to collect content validity evidence and response process validity through expert evaluation and cognitive interviews. Method: The adaptation process of the measurement tool of the IPP30 followed the guidelines of the International Test Commission up to the development stage, which is the second phase after the pre-condition. The development stage included: 1) translation using the forward-backward translation method, 2) collection of content validity evidence through expert evaluations, and 3) collection of response process validity evidence through cognitive interviews with eligible participants. Findings: The results demonstrated that the Indonesian version of IPP30 possesses both content validity and response process validity, supporting its use to measure the impostor phenomenon in Indonesia. The validity evidence obtained serves as an initial foundation for testing this scale on a larger sample to verify its psychometric properties. Implication: This study represents an initial validation step to provide a measurement tool that can be used to assess the impostor phenomenon, which can be beneficial for related research in Indonesia.